Kebijakan Formulasi Tindak Pidana terhadap Pelaku Usaha yang Tidak Melaksanakan Putusan KPPU yang Sudah Inkracht - Citrawan, Fitrah Akbar (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2019)
Article 44 paragraphs (4) and (5) of Law no. 5 of 1999 regulates that for business actors who do not carry out the KPPU's decisions that have permanent legal force (BHT), KPPU can hand over these business actors to investigators. The provision is unclear, that is, it is not written / stated explicitly, including the categories of acts that can be subject to / threatened with principal or additional crimes as in Articles 48 and 49 of Law No. 5 of 1999. The lack of clarity is related to the issue of formulasi policy which is one of the strategic policies in realizing more rational laws and becomes a guideline for the next functionalization stages, namely the application and execution stages. Formulation of criminal offenses in Article 48 paragraphs (1) and (2) of Law no. 5 of 1999 is interpreted as a wesenschaw offense, which is said to have fulfilled the elements of a criminal offense not only because the act is in accordance with the formulation of a criminal offense but the act is also intended by the legislators, that the business actor and or other party may be convicted if do not carry out what becomes their obligation as in the KPPU Decision which has BHT. Obligations to carry out the business and other parties mentioned, namely carrying out administrative sanctions / actions imposed by KPPU for violating the administration of Law No. 5 of 1999. That also signifies criminal conviction in Article 48 paragraphs (1) and (2) of Law no. 5 of 1999 is ultimum remidium.